Effective Fuzzy Logic Control of a Stand-alone Photovoltaic Pumping System - M. Bahloul; L. Chrifi Alaoui; M. Souissi; M. Chaabane; S. Drid (the Journal of Renewable Energy Research, 2015)
This paper presents an effective control of a stand-alone batteryless photovoltaic (PV) pumping system. The whole design (configuration and control) is oriented in order to minimize the cost and maximize the effectiveness, the efficiency and the reliability of the whole system. Beyond the withdrawal of the battery and the rotor speed sensor, the system is composed only of a DC-DC boost converter, a DC-AC inverter, an Induction Motor (IM) and a centrifugal pump. In order to control the dc-link voltage and maximize the efficiency of the IM, a Fuzzy Logic Controller (FLC) is introduced. The validity and the effectiveness of the proposed FLC is tested and confirmed by a simulation under various climate changes.